A case report of fatal familial insomnia with cerebrospinal fluid leukocytosis during the COVID-19 epidemic and review of the literature - Zheng Wang; Yueqi Huang; Shuqi Wang; Jiefang Chen; Gesang Meiduo; Man Jin; Xiaoying Zhang (Prion)
Fatal familial insomnia (FFI) is a rare autosomal dominant genetic neurodegenerative disease. Generally, FFI patients will develop rapidly progressive dementia, sleep disturbance, autonomic dysfunction, and so on. Cerebrospinal fluid examination of FFI patients normally shows no obvious abnormalities. Here, we report a young male patient who was diagnosed with FFI during the COVID-19 epidemic. Clinical symptoms include psychobehavioral abnormality, cognitive decline, sleep disturbance, and autonomic dysfunction. No abnormalities were found in routine examinations after admission. However, the number of white blood cells in the cerebrospinal fluid increased. Though the patient was treated with anti-infection and immunotherapy, the symptoms were not relieved. A lumbar puncture was performed again, and it was found that the total Tau protein in the cerebrospinal fluid was elevated, and PET results showed that brain metabolism decreased. Finally, a genetic test was used to confirm the diagnosis of FFI. This case suggests that patients with FFI may also have elevated white blood cells in cerebrospinal fluid and timely detection of Tau protein in cerebrospinal fluid is helpful for early identification of FFI. And precise diagnosis relies on genetic testing.